A study on the factors of job turnover intention in Malaysia retail industry - Cheah, Wan Teng; Lim, Pei Ru; Low, Shi Kee; Tan, Xiao Fern; Yew, Yan Yee (2019)
Retail industry is one of the important core driver of Malaysia economy which contribute to the growth of Malaysia’s economy as well as GDP. Employees of the service organisation have responsibility to play critical role to maintain the contribution of Malaysia economy by decreasing the turnover issues and determine the performance of the organisation. Job turnover intention in retail industry has been found that increasing over the time. Hence, the aim of this research is to investigate the factors (pay and reward, co-worker support, training and development as well as job stress) that affect job turnover intention in Malaysia retail industry. Previous studies found that there have significant impact on job turnover intention in Malaysia retail industry. In this research, researchers conduct the survey to gather the primary source by distributing 450 with online questionnaire to the target population in selected area in Malaysia retail industry. Researchers conducted the Cronbach’s alpha reliability test on every constructs which resulted high reliability test. Moreover, Pearson correlation coefficient and multiple regression revealed the importance of four independent variables. In the results show three independent variables which included pay and reward, co-worker support, training and development have a negative relationship whereas job stress has a positive relationship with dependent variable (job turnover intention). Retail managers should implement proper strategy which would increase retention of employees and reduce their job turnover intention. Overall of the research tends to provide investigate the causes which affecting the job turnover intention in Malaysia retail industry. Throughout this research, the limitations of the study have been identified. Hence, it should be avoided the similar limitation in the future research. Besides limitation, the discussion of findings, implications of the study and recommendations for future research will be conducted in the end of this study.